Evolutionary analyses and expression patterns of TCP genes in Ranunculales - Damerval, Catherine; Claudot, Carmine; Le Guilloux, Martine; Conde e Silva, Natalia; Brunaud, Véronique; Soubigou-Taconnat, Ludivine; Caius, José; Delannoy, Etienne; Nadot, Sophie; Jabbour, Florian; Deveaux, Yves (Frontiers in Plant Science, 2022)
TCP transcription factors play a role in a large number of developmental processes and are at the crossroads of numerous hormonal biosynthetic and signaling pathways. The complete repertoire of TCP genes has already been characterized in several plant species, but not in any species of early diverging eudicots. We focused on the order Ranunculales because of its phylogenetic position as sister group to all other eudicots and its important morphological diversity. We characterized the full set of TCP transcripts in Nigella damascena (Ranunculaceae) and found that they are the orthologs of the TCP genes previously identified from the fully sequenced genome of Aquilegia coerulea. Phylogenetic analyses combined with the identification of conserved amino acid motifs suggest that six paralogous genes of class I TCP transcription factors were present in the common ancestor of angiosperms. We highlight independent duplications in core eudicots and Ranunculales within the class I and class II subfamilies, resulting in different numbers of paralogs within the main subclasses of TCP genes. This has most probably major consequences on the functional diversification of these genes in different plant clades. The expression patterns of TCP genes in Nigella damascena were consistent with the general suggestion that CIN and class I TCP genes may have redundant roles or take part in same pathways, while CYC/TB1 genes have more specific actions. Our findings open the way for future studies at the tissue level, and for investigating redundancy and subfunctionalisation in TCP genes and their role in the evolution of morphological novelties.